Defining danger : American assassins and the new domestic terrorists - Clarke, James W., 1937- (New Brunswick, N.J. : Transaction Publishers, 2007)
"In Defining Danger, James W. Clarke explores the cultural and psychological linkages that define assassinations and a new era of domestic terrorism in America."--BOOK JACKET.
Includes bibliographical references (p. 385-399) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Terrorists -- United States -- Biography; Domestic terrorism -- United States; Assassination -- United States; Assassins -- United States -- Biography; Electronic books